Mental toughness and overtraining behaviours - Tibbert, S. J. (2013)
The idea of mental toughness (MT) is bewitching. The construct is consistently associated with success and being able to overcome great difficulties while demonstrating dogged perseverance regardless of adversity (Gucciardi, Gordon, & Dimmock, 2008; Jones, Hanton, & Connaughton, 2002). It is no wonder sport psychology researchers strive to understand how to develop and display MT. The increase in published research in this topic attests to the popularity of becoming mentally tough. A clear understanding of MT, what it does and does not enable athletes to do, however, has not yet arrived. The purpose of this thesis was to gain an understanding of MT, with specific attention paid to the relationship with stress/recovery imbalance (SRI). Given that many risk factors associated with SRI are the same characteristics associated with being mentally tough, investigating the relationship between SRI and MT seemed an important first step in the research. In Study 1, I investigated how MT correlated with stress/recovery in 107 athletes. The athletes completed the Mental Toughness Inventory (MTI; Middleton, 2005) and the Recovery-Stress-Questionnaire for Athletes (RESTQ-Sport; Kellmann & Kallus, 2001) to determine if the attributes measured on the MTI have any associations with the scales of the RESTQ-Sport. Only three attributes on the MTI had adequate test-retest reliability: potential, mental self-concept, and task familiarity. Correlations were carried out only with the three MT attributes with acceptable reliability. The potential subscale displayed a moderate positive linear correlation with sport-specific recovery indicating that at the highest scores of potential, athletes reported more sport-specific recovery. The MT attributes of mental self-concept and task familiarity displayed moderate curvilinear correlations with sport-specific recovery scales of the RESTQ-Sport. The curvilinear correlations reflect decreasing recovery at the highest levels of MT. The results suggest that some attributes of MT may relate to increased ability to recover whereas other attributes are associated with lower recovery. To understand the relationship between MT and SRI in more detail, I interviewed four junior and four senior footballers and three football coaches focusing, in particular, on athletes` stories of MT, SRI, situations where they felt they demonstrated their MT, and how attributes may have helped or hindered them in sport and in a wider sense, life outside sport. I used a narrative approach to analyse and present the data, which aggregated into two constructed fictional stories. The results from this study identified numerous risk factors in the overtraining (OT) risks and outcomes model (Richardson, Andersen, & Morris, 2008) that were viewed in the football culture as MT. To gain more information regarding the benefit or detriment of trying to be mentally tough in football, I used a case study approach to follow two footballers through a competitive season. I obtained a variety of data through a combination of quantitative and qualitative methodologies to uncover various sociocultural factors deemed mentally tough that led to SRI. In the general discussion, it is clear that MT is different things to different people, as a number of researchers have suggested (Bull, Shambrook, James, & Brooks, 2005; Crust, 2008; Fawcett, 2011). It also appears that MT is different for different sporting cultures and may be as much culturally determined as having something to do with individual differences. In the professional team I studied in depth, there were culturally transmitted MT ideals and expectations of "no pain no gain," "suck it up," "don`t show vulnerability," silence your emotions," "play while injured," "give 110%," and many other attitudes and behaviours that seemed to increase the risk of SRI. In this research, which focussed on one sport, MT appears to be many conflicting ideas, attributes, and behaviours, some of which are beneficial to athletes and their performances, but some that may be pathogenic for athletes who struggle to fit into the MT mould.